To post or not to post: psychological and ethical concerns = (to post or not to post: kebimbangan psikologi dan etika) - Abdul Azmil, Ameerah; Borhan, Lihanna; Periasamy, Venisry; Abu Hassan, Shakinah (Association of Researcher of Skills and Vocational Training, Malaysia, 2024)
This review digs into the multiple phenomena of sharenting, which is a challenging part of contemporary parenting in the digital era . As parents increasingly share their children's lives online, the discussion centres on the ethical considerations surrounding sharenting, particularly concerning pre-verbal children. The exploration navigates the delicate balance between parents' right to share, potentially paving the way for a stable future income for their children, and children's right to privacy, evoking feelings of deception when their lives are extensively documented without their awareness. The review underscores the importance of ethical decision-making, advocating for a nuanced understanding of sharenting that acknowledges its non-one-size-fits-all nature, instead, it emphasizes the need for careful consideration based on individual circumstances. Ultimately, this review aims to contribute to a more comprehensive understanding of the ethical implications of sharenting in today’s digital era.